The Future of Artificial Intelligence in Interactive Learning: Trends, Challenges, Opportunities - Teguh Hidayat Iskandar Alam; Ika Safitri Windiarti (Engineering Proceedings)
This study explores how artificial intelligence (AI) will evolve and impact interactive learning models in the next two decades. Using a PRISMA-based Systematic Literature Review (SLR) approach, the study analyzes articles published in the last five years to identify trends, challenges, and opportunities for AI applications in education. The results show that AI has the potential to create adaptive, personalized, and immersive learning systems, while supporting the development of a more inclusive and multidisciplinary education ecosystem. The findings also show how AI can synergize with technologies such as virtual reality (VR) and augmented reality (AR), and contribute to sustainability, decision-making, and professional education. In addition, the study identifies the social, economic, and cultural impacts of AI adoption, and provides recommendations to mitigate challenges, such as data privacy and technology access. By providing new insights into future trends in AI in education, this study offers a basis for developing innovative and sustainable education policies and practices to meet global needs.